Eksistensi Underpricing Saham Initial Public Offering (IPO) - Sianturi, Ivan Gunawan (Keizai, 2024)
Companies raise funds not only through debt but also by offering shares to the public, known as an Initial Public Offering (IPO). A common phenomenon in IPOs is underpricing, where the initial offering price is lower than the secondary market price. Despite the economic instability caused by COVID-19, some companies still proceeded with IPOs. This study analyzes the existence of underpricing in IPOs on the Indonesia Stock Exchange (IDX) during the COVID-19 pandemic. The sample includes companies that went public between March 9, 2020, and June 30, 2021, using cross-sectional regression analysis. The findings confirm that underpricing persisted during the pandemic, mainly due to company performance reported in the prospectus. Despite the crisis, some companies maintained strong financial performance, attracting investors. Additionally, oversubscription contributed to underpricing, as low IPO prices combined with high company performance led to excessive demand. Interestingly, even companies with higher IPO prices experienced oversubscription, indicating strong investor interest despite market uncertainties.